Depression and health literacy among adolescents and adults in Germany: findings from two representative samples - König, Lars; Schröder, Rebekka; Hamer, Tim; Suhr, Ralf (Frontiers in Psychology, 2024)
Introduction Depressive disorders constitute a significant public health challenge. Health literacy might be an important factor to consider in prevention strategies for depressive disorders, which is why this study aimed at exploring the association between depressive symptom levels and severity and health literacy, along with additional sociodemographic factors. Materials and methods Data were collected from two large samples of adults (N = 3,011) and adolescents (N = 1,021) representative of the German-speaking population in Germany. Levels of health literacy (HLS-EU-Q16 questionnaire), depressive symptom severity, rates of depression levels (PHQ-9 questionnaire) and sociodemographic information (age, gender, social status, level of education) were obtained. The associations between sociodemographic factors, health literacy and depression were analyzed using t-tests, analyses of variance and χ2-tests. Results Overall, rates of depression were high in both samples (16.5% in adults and 18.4% in adolescents) when measured with the sum score ≥ 10 cut-off criterion and substantially lower when assessed with the diagnostic algorithm criterion (7.2% in adults and 9.8% in adolescents). Rates of depression and severity of depressive symptoms were higher in female than male individuals in both samples. Depressive symptom severity and depression rates increased with increasing age in adolescents and decreased with increasing age in adults. Higher levels of education and lower social status were associated with higher depressive symptom severity and rates in adults, with a more heterogeneous picture in adolescents. In both samples, depressive symptom severity and rates were higher in individuals with poorer health literacy. Discussion The results point to a potential role for health literacy in preventing depressive disorders. More research is needed with longitudinal and experimental study designs into the question whether public health interventions targeting health literacy improvements could play a critical role in reducing the burden of depression across different age cohorts.